1991
DOI: 10.1111/j.1471-4159.1991.tb03450.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Brain Nicotinic Receptors by Chronic Agonist Infusion

Abstract: Several studies have demonstrated that chronic treatment with nicotine elicits an increase in the number of brain nicotinic receptors. To determine whether this effect is elicited by other nicotinic agonists found in tobacco, the effects of chronic infusion with nicotine on brain nicotinic receptors were compared with those after anabasine and lobeline. C57BL/6 mice were infused with saline or equimolar doses (18.5 mumol/kg/h) of nicotine, anabasine, or lobeline for 8 days. Nicotinic receptors, quantified by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Also, chronic infusion of anabasine produced an increase of high-affinity nicotinic sites in mice (Bhat et al 1991). Furthermore, studies in cells and cell lines have shown that some nicotinic agonists can induce up-regulation of α4β2-nAChRs Whiteaker et al 1998;Fenster et al 1999b).…”
Section: Up-regulation Of Neuronal Nachrs Induced By Agents Other Thamentioning
confidence: 99%
“…Also, chronic infusion of anabasine produced an increase of high-affinity nicotinic sites in mice (Bhat et al 1991). Furthermore, studies in cells and cell lines have shown that some nicotinic agonists can induce up-regulation of α4β2-nAChRs Whiteaker et al 1998;Fenster et al 1999b).…”
Section: Up-regulation Of Neuronal Nachrs Induced By Agents Other Thamentioning
confidence: 99%
“…In contrast, isoarecolone is reported to be less efficacious than nicotine in releasing [3H]-dopamine from rat frontal cortex (Whiteaker et al, 1995 (Aizenman et al, 1991). Lobeline fails to mimic nicotine in tests of conditioned place preference (Fudala & Iwamoto, 1986), discriminative stimulus properties Reavill et al, 1990a), and locomotor activity , and receptor binding upregulation (Bhat et al, 1991). These differences are probably not due to inadequate central penetration (Reavill et al, 1990a;Bhat et al, 1991).…”
Section: Comparisons Between Agonist-evoked [3h]-dopamine and [3h1-namentioning
confidence: 74%
“…Lobeline fails to mimic nicotine in tests of conditioned place preference (Fudala & Iwamoto, 1986), discriminative stimulus properties Reavill et al, 1990a), and locomotor activity , and receptor binding upregulation (Bhat et al, 1991). These differences are probably not due to inadequate central penetration (Reavill et al, 1990a;Bhat et al, 1991). Possibly the only evidence that lobeline can activate brain nicotinic AChRs is a report that lobeline-evoked [3H]-dopamine release from mouse striatal synaptosomes is partially mecamylamine-sensitive (Grady et al, 1992).…”
Section: Comparisons Between Agonist-evoked [3h]-dopamine and [3h1-namentioning
confidence: 99%
“…If nAChR upregulation is due to receptor desensitization, prolonged treatment with α7 agonists may be associated with changes in the magnitude and/or duration of receptor desensitization, leading to a gradual diminution of receptor upregulation. Previous studies with rats and mice have generally concluded that nicotinic receptor up-regulation increases as the duration of agonist exposure becomes longer (Bhat et al, 1991;Collins et al, 1990;Marks et al, 1983;Marks et al, 1985;Pauly et al, 1991) and results from our own lab showed upregulation of mouse brain BTX binding following nicotine exposure for 30 days via the drinking solution (Sparks and Pauly, 1999). Another possible reason that choline fails to sustain α7 nAChR upregulation beyond 14 days may be a developmental change in the number and/or efficacy of blood-brain barrier choline transporters.…”
Section: Discussionmentioning
confidence: 99%